Saúde mental e trabalho docente: uma análise crítica das condições laborais e as perspectivas de intervenção da Lei Nº 14.681/2023. - Eliane Magni Soares (Revista ft, 2026)
The present study addresses the mental health of Basic Education teachers, highlighting the incidence of psychological disorders arising from professional practice. In the current scenario, characterized by progressive demands, deterioration of labor relations, excessive administrative requirements, and the social devaluation of the career, there is an emerging need to investigate the variables that catalyze the mental exhaustion of these professionals. A qualitative bibliographic review research was conducted. The scope of the investigation encompasses chronic occupational stress, anxiety disorders, depressive episodes, and Burnout Syndrome, evaluating the repercussions of such conditions on both the personal and professional spheres of teachers. The role of educational institutions and the State is discussed through the lens of the urgent need to implement psychosocial support networks, effective occupational medicine programs, and public policies focused on preserving the worker's mental integrity, coordinating the advancements of Law No. 14,681/2023 and the complementary guidelines of Law No. 14,819/2024. By analyzing different theoretical approaches to the psychopathology of work, the research demonstrates that teacher illness compromises the school climate, raises absenteeism rates, and makes the pedagogical bonds established with students precarious. It is concluded that addressing this crisis must not be restricted to individualized self-care actions, but rather demands a profound restructuring of the material, organizational, and contractual conditions of Brazilian school networks.